377. Use of Mid-Turbinate Swab (MTS) versus Throat Swab (TS) for Detection of Respiratory Pathogens in Children, Kansas City, Missouri, November 2015 – May 2019. (15th December 2022) - Banerjee, Dithi; Lee, Brian R; Harrison, Christopher J; Lively, Joana Y; Whitaker, Brett; Zhou, Yingtao; Selvarangan, Rangaraj
Abstract: Background: An optimal specimen collection method is important for pathogen detection in respiratory surveillance studies. Mid-turbinate swab (MTS) in combination with throat swab (TS) were used for collecting samples from children enrolled in Kansas City site of the New Vaccine Surveillance Network (NVSN), a prospective surveillance network for acute respiratory infections. A standalone MTS is used for standard of care (SOC) testing. We compared detections from NVSN MTS+TS vs. SOC MTS samples collected ±1 day of each other to evaluate the sensitivity of the single MTS collection in children. Methods: Nucleic acid extracts from NVSN MTS+TS samples were tested by Luminex NxTag Respiratory Pathogen Panel (NxTag RPP). SOC MTS samples were tested by BioFire® Respiratory Panel 1.7. (FilmArray). All children, aged < 18 years enrolled in the inpatient and Emergency Department for NVSN (November 2015 to May 2019) with available historical MTS SOC testing results ±1 day of enrollment were included in the study. Concordance between results of NVSN MTS+TS and SOC MTS testing was measured. Results: Paired NVSN and SOC samples were available from 315 subjects with median age of 16.8 months (IQR 5.0 months – 61.7 months); 59.3% (189/315) were from male subjects. An overall positivity of 93.6% was noted with 295 detections by one sample or the other. Of the 295 detections, 231 (78%) detections were in both samples; 35 (12%) detections by MTS+TS; and 29 (10%) detections by MTS only. High concordance ( >90%) and very good Kappa values (Table 1) between the 2 specimen collection methods was noted for most pathogens. 72% of discrepant samples were from children with median age 13.2 months (IQR 8.0 months – 38.6 months). Conclusion: We observed high concordance between MTS and MTS+TS for all targets. Most discrepant samples were from young children in whom adequate sampling can be challenging, perhaps reducing sensitivity. Differences in time of collection and testing, and platform differences (NxTag RPP vs. FilmArray) may have impacted our data, e.g. due to variable assay sensitivities for specific targets. Regardless of these differences, our data show comparable performance between MTS alone and MTS+TS suggesting that MTS alone may be sufficient for respiratory pathogen surveillance in children. Disclosures: Brian R. Lee, PhD, MPH, CDC: Grant/Research Support|Merck: Grant/Research Support Christopher J Harrison, MD, Astellas: Grant/Research Support|GSK: Grant/Research Support|Merck: Grant/Research Support|Pediatric news: Honoraria|Pfizer: Grant/Research Support Rangaraj Selvarangan, BVSc, PhD, D(ABMM), FIDSA, F(AAM), BioFire: Grant/Research Support|Luminex: Grant/Research Support.